Assessment of the toxicity of firefighter exposures using the PAH CALUX bioassay - Beitel, Shawn C. (2021)
Firefighters can be exposed to a complex set of contaminants while at a fire scene. Identifying new ways to monitor and assess exposure, particularly relating to toxicity is essential to determine the effectiveness of intervention techniques to reduce exposure. This study investigated the use of the polycyclic aromatic hydrocarbon (PAH) CALUX® bioassay for the assessment of exposure and associated toxicity firefighters might encounter. This was done through analysis of extracts of dermal wipes and urine samples collected from firefighters before and after a controlled fire. An increased bioassay response was observed from post-fire neck and calf samples, indicating a greater concentration of PAH-like compounds on the skin. The use of a baby wipe to clean the face and neck during rehab resulted in the attenuation of the observed bioassay response from the neck post-fire. Though a correlation was observed between the bioassay response and hydroxylated PAH concentrations found in the urine, the increased bioassay response from the post-fire urine samples was likely due to unknown compounds other than the hydroxylated PAHs tested. Our results suggest that this bioassay provides a useful measure of firefighter exposure, particularly relating to the potential toxicity of contaminants.